O projeto profissional do serviço social na defesa e garantia de direitos da pessoa com deficiência: espaço de resistência e luta na Cidade de São José dos Campos - Gomes, Fábio Alexandre (2017)
The present study deals with the professional performance of social workers who work in care institutions for people with disabilities in the municipality of São José dos Campos in the metropolitan region of Vale do Paraiba. The research was carried out with the Social Service professionals and that they are organized in a collective way through the Group of Entities of Attendance to Person with Disability the GRUPO PcD. The Organization of the research occurred through the choice of research methodology that had one of the objectives to establish contact with subjects who act and reflect the professional practice in their entities, but also organize themselves collectively in a discussion group regarding the service network. The research was divided into two phases: the first, by sending a questionnaire containing closed and open questions about professional training and the professional practice of social workers. The second phase, through the collection of testimony recorded and filmed using the methodology of the focal group and transcribed with subjects of the group. In the realization of the research, I found subjects with different characteristics and positions regarding professional practice, in this way I valued the content of the narratives, maintaining the focus of professional practice and guaranteeing and defending the rights of the disabled person. I used the qualitative approach to analyze the data and it is possible to identify and analyze that the construction of the dialogue of practice with the professional doing and the construction of positioning that try to carry out the construction of a society that fights for the consolidation of the rights of people with disabilities. The individual or collective professional practice of reveals as a constant space of resistance and struggle the subjects reveal that the complexity of social relations is present daily in the professional doing. Recognizing the professional practice of the social worker as a space for the production of resistance and the struggle for the rights of persons with disabilities reveals and strengthens possibilities for professional practice in the face of the demands of contemporary capitalist society